Examining the use of Jamovi in learning statistics: Students’ perception - Jumroh, Jumroh; Ningsih, Yunika Lestaria; Octaria, Dina; Nopriyanti, Tika Dwi (Universitas Islam Raden Intan Lampung, INDONESIA, 2025)
Purpose: The present study explores how pre-service teachers engage with Jamovi, an open-source platform for statistical analysis, during their study of descriptive statistics. It investigates students’ perceptions regarding its functionality, its impact on conceptual understanding, and the external conditions that shape their experiences in a digital learning context. Method: Employing a concurrent mixed-methods approach, the research involved 72 undergraduate students enrolled in a teacher training program in Indonesia. Data were gathered using structured questionnaires complemented by classroom observations conducted across seven instructional sessions where Jamovi was actively integrated into the teaching process. Findings: Students demonstrated strong engagement and generally favorable perceptions toward Jamovi, citing its user-friendly interface and real-time visual feedback as major advantages. The study also found that students' experiences were influenced by factors such as the availability of instructional guidance and reliable internet connectivity. Significance: The findings indicate that Jamovi offers a viable alternative for enhancing statistical instruction, particularly for learners with minimal prior exposure to analytical tools. By lowering technical barriers, it supports independent learning and could be instrumental in developing data literacy among prospective educators. This research highlights the value of adopting accessible digital tools alongside pedagogical support to improve student outcomes in statistics education.